Determination of Nitrazepam in its pure form, formulations and in biological samples - Upadhyay, Kanchan (Recent Research in Science and Technology, 2012)
A simple and sensitive spectrophotometric determination method for the determination of nitrazepam in bulk, in pharmaceutical dosage forms and in biological fluids was developed. The method is based upon reduction of nitro group of nitrazepam by zinc and hydrochloric acid followed by diazotization and coupling with orcinol in basic medium to form a stable chromophore which absorbs at 470 nm. The method showed a good linearity in the range 0.3 – 3.5µgmL-1. The method is free from the interference of common excipients used in pharmaceutical dosage. The method was also used for the determination of nitrazepam in pharmaceutical as well as in biological samples.